THE INFORMATION LITERACY HOW TO DISCIPLINE IN THE CURRICULUM LIBRARIANS TRAINING IN SPAIN AND BRAZIL - Mata, Marta Leandro da; Silva Casarin, Helen de Castro [UNESP]; Angel Marzal, Miguel (Edit Um-ediciones Univ Murcia, 2016)
The aim of this study was to how the disciplines of information literacy have been addressed in the courses of Information and Documentation in Spain and Librarianship in Brazil, in order to characterize the main contents. In this sense, there was a research of a qualitative nature and documentary, analyzing the curricula and syllabi of these courses in both countries. Using content analysis, it was found that the content of these modules in Brazilian courses is divergent, while in the Spanish case they are focused on the formation of future educators. It was concluded that in Brazil the integration of information literacy topics is still being consolidated. In Spain, there is a higher incidence of courses that include this content, and it is noticeable that there is a certain consensus on how this issue is addressed in courses. Promoting exchange and further discussion between the two countries may be enriching, and strengthen the subject, especially in Brazil.
Keywords: Information literacy; librarianship; curricula; undergraduate courses